Measurement and assessment of mobile network electromagnetic radiation pollution in Ramadi, Iraq - Mohammad S. Zidan; Mohammed Qasim Taha; Linha Abdulhameed Yaseen; Namariq Dawood Hameed; Qais N. Abid (Bulletin of Electrical Engineering and Informatics, 2022)
The electromagnetic radiation produced by cellular towers in Ramadi city, west of Iraq, is measured and analyzed in this research. This contains basic nodes, hub repeaters, and feeders for transmitting the carrier throughout the entire Ramadi city as well as the surrounding areas. As a result, this research focused on this area to measure and assess energy to determine if it is safe for people or has over the danger threshold. The study region was split into fifty-five mobile phone tower locations. In general, electric field intensity levels surpass 1.7 V/m, which is dangerous and should be reduced. However, apart from a few sites (2, 3, 35, 36, 45, 51, and 53), the magnetic field intensity and radiation density are acceptable based on the findings. The energy severity criteria are based on LATNEX corporation's guidelines.